Fortune's rocks : a novel - Shreve, Anita (Boston : Little, Brown and Company, 1999)
In 1890s Boston, a 15-year-old upper-class girl is banished to a convent following an affair with a married doctor which left her pregnant. The girl is forced to surrender the child for adoption, but she subsequently goes to court to recuperate it, and eventually marries the doctor. A study in the mores and manners of the day.
Keywords: Young women -- Sexual behavior -- New England -- Fiction; Love stories